Method for preparing silicon carbide aerogel under low-temperature condition
By introducing dry ice and carbon dioxide gas in the low-temperature preparation process of silicon carbide aerogel, its pore structure and porosity are regulated, the problem of poor mechanical properties of silicon carbide aerogel in the prior art is solved, and high porosity and low porosity are achieved Silicon carbide aerogel material with thermal conductivity and good mechanical properties.
Patent Information
- Application Number
- CN202411431678.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
The existing silicon carbide aerogel preparation technology is difficult to simultaneously improve porosity, reduce density and thermal conductivity, and the mechanical properties are poor, which affects its practical application.
Silicon carbide aerogel is prepared under low temperature conditions. By introducing dry ice and carbon dioxide gas, the pore structure and porosity of the aerogel are regulated, the thermal conductivity is reduced, and the mechanical properties are improved. Specific steps include sol preparation, gel molding, aging treatment, drying and high-temperature heat treatment.
It achieves high porosity, low thermal conductivity and good mechanical properties of silicon carbide aerogel. It is suitable as a high-performance insulation material, and has a simple process and cost-saving.
Smart Images

Figure CN119284908A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of aerogels, and in particular to a method for preparing silicon carbide aerogels under low temperature conditions. Background Art
[0002] Silicon carbide aerogel is an advanced material with many excellent properties. It is lightweight and has excellent thermal insulation, mechanical properties, high temperature resistance, oxidation resistance, selective adsorption of organic solvents, electromagnetic wave absorption performance and high porosity. It is often used in aerospace, automotive batteries, precision device insulation, catalyst carriers, filter materials, high-temperature insulation materials, electromagnetic wave absorption materials and other fields.
[0003] In the existing silicon carbide aerogel preparation technology, carbosilane is usually mixed with a polymer and then directly sintered at high temperature. However, the internal pore structure of the silicon carbide aerogel obtained by this method is randomly formed, the density is large, the porosity is low, and the thermal conductivity is relatively large. Another method is to mix a silicon source and a carbon source to prepare a preform, and then sinter it at high temperature under an inert environment. Although it can increase the porosity, reduce the density and thermal conductivity, the mechanical properties of the obtained silicon carbide aerogel are poor, it is brittle, and is not conducive to practical applications.
[0004] Therefore, increasing the porosity of silicon carbide aerogel materials, reducing density and thermal conductivity while improving their mechanical properties are technical issues that need to be solved urgently. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for preparing silicon carbide aerogel under low temperature conditions. By introducing dry ice in the aerogel preparation process, not only the temperature is reduced to control the reaction rate, but also carbon dioxide gas is added to the sol preparation system, thereby achieving the purpose of regulating the pore structure, pore volume and porosity of the aerogel, reducing the thermal conductivity and improving its mechanical properties.
[0006] The specific technical solutions are as follows:
[0007] A method for preparing silicon carbide aerogel under low temperature conditions comprises the following steps:
[0008] S1. dissolving hydroquinone in a mixture of water and ethanol, and stirring to obtain a solution A;
[0009] S2, uniformly mixing formaldehyde, silicate and 3-aminopropyltriethoxysilane to obtain solution B;
[0010] S3, providing an incubator with an ambient temperature of -80 to 10°C, placing crushed dry ice particles in the incubator, then slowly pouring solution A and solution B into the incubator, stirring and mixing to form a sol;
[0011] S4, after the mixed sol is gelled, it is subjected to aging treatment, and then replaced with an alcohol solvent and dried at normal pressure;
[0012] S5. Finally, high temperature heat treatment is performed to obtain silicon carbide aerogel.
[0013] The preparation process of aerogel is generally divided into the steps of sol preparation, gel forming, drying and heat treatment. Among them, the regulation of pore structure and porosity is mainly carried out in the sol preparation and gel forming stages. Among them, steps S1 and S2 belong to the sol preparation stage, and step S3 belongs to the gel forming stage. In the sol preparation stage, the pore structure and porosity can be regulated by selecting appropriate solutes, solvent types and solute and solvent component ratios to control the concentration and viscosity of the sol. Introducing dry ice in the gel forming stage can not only reduce the temperature to control the reaction rate, but also add carbon dioxide gas to the sol preparation system. The present invention plays a proper role in promoting the regulation of pore structure and porosity by controlling the gel system and introducing dry ice.
[0014] Furthermore, the catechol described in step S1 is one or more of hydroquinone, resorcinol or catechol;
[0015] It should be noted that the chemical formula of hydroquinone is C6H6O2. As a cross-linking agent, it can react with silicate, 3-aminopropyltriethoxysilane and other substances to form a three-dimensional network structure, which can affect the basic skeleton characteristics of aerogel. Different structures of hydroquinone will make the basic skeleton of aerogel different, resulting in different pore structures, porosity, thermal conductivity and mechanical properties of the final silicon carbide aerogel.
[0016] Furthermore, hydroquinone is selected from resorcinol. The water in step S1 is one of deionized water, distilled water or ultrapure water. Water and ethanol are used as solvents to help dissolve and disperse resorcinol. At the same time, ethanol is easy to volatilize in the subsequent normal pressure drying process, which helps to form a porous structure. In particular, the weight ratio of water to ethanol is 1: (10-20).
[0017] Furthermore, the weight ratio of the hydroquinone, formaldehyde, silicate and 3-aminopropyltriethoxysilane is (2-3):(1-3):(4-9):(1-4).
[0018] It should be noted that formaldehyde, as a cross-linking agent, can react with resorcinol, ethyl orthosilicate and 3-aminopropyltriethoxysilane, thereby enhancing the stability and mechanical strength of the aerogel. Formaldehyde and hydroquinone can be used together as cross-linking agents. Too high a cross-linking agent content will reduce the porosity of the aerogel, because too many cross-linking points make the gel network dense, hindering the formation of macropores, thereby reducing the pore space. Conversely, if the cross-linking agent content is too low, it may not be enough to form a stable three-dimensional network structure, so that the aerogel is easy to break during the molding process, and the mechanical properties of the aerogel, such as compressive strength and toughness, will be significantly reduced. Therefore, the proportion of the cross-linking agent should be appropriate.
[0019] Furthermore, the silicate in step S2 is one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or butyl orthosilicate; silicate, as a silicon source, is a key raw material for forming silicon carbide aerogel, and its hydrolysis and condensation reactions will generate -Si-O-Si- bonds that cross-link with each other to construct the skeleton structure of the aerogel.
[0020] Furthermore, the stirring in step S3 is magnetic stirring, and the stirring time is 20 to 30 minutes; the size of the dry ice particles is about 0.5×0.5×0.5 cm 3 ~1×1×1cm 3 The insulated box providing an ambient temperature of -80~10°C can be achieved by using a foam box filled with dry ice or placing the insulated box in other low-temperature environments to maintain the ambient temperature at -80~10°C.
[0021] It should be noted that dry ice is a solid form of carbon dioxide. Dry ice particles sublimate in a mixed solution to form cold air bubbles, and the substance in the bubbles is carbon dioxide gas. Carbon dioxide gas is heavier than air. When the mixed solution to which dry ice is added is stirred, the sinking carbon dioxide gas dissolves more and more into the sol system as it is stirred. Smaller dry ice particles have a larger surface area, and the rate of forming cold air bubbles in the mixed solution is faster, which effectively keeps the mixed solution at a low temperature and slows down the sol forming rate, which is conducive to the formation of silicon carbide aerogel with uniform pore size. At the same time, dry ice has stable chemical properties, is odorless and non-toxic, is easy to sublimate at room temperature, has high heat of vaporization, and can rapidly reduce the surrounding temperature when it sublimates at normal pressure. By placing appropriate amounts of dry ice inside and outside the incubator, not only can the reaction temperature be reduced to control the reaction rate, and the speed of preparing and forming the silicon carbide aerogel sol can be controlled, but also the volatilization of reagents such as formaldehyde and ethanol in the reaction system can be reduced at low temperatures. Dry ice can also produce carbon dioxide gas to form bubbles when it meets water, which helps to form a uniform microporous structure, thereby increasing the porosity. The influence of dry ice on sol structure is mainly reflected in the following aspects:
[0022] 1) The low temperature environment of dry ice can slow down the rate of chemical reactions in the sol. During the preparation of the sol, the reaction rate of components such as hydroquinone, formaldehyde, ethyl orthosilicate, and 3-aminopropyltriethoxysilane will slow down due to the decrease in temperature, which is conducive to the formation of a more uniform and stable gel network and avoids the uneven pore structure caused by rapid gelation, which helps to form a more delicate and regular pore structure.
[0023] 2) Dry ice sublimates rapidly when it comes into contact with water molecules, producing carbon dioxide gas, which forms tiny bubbles in the sol. These bubbles are fixed during the gelation process, helping to form evenly distributed pores. These pores are retained during the drying process, thereby increasing the porosity of the aerogel.
[0024] 3) Under low temperature conditions, the generation and distribution of bubbles are more uniform, which reduces the volatilization of reagents such as formaldehyde and ethanol in the reaction system, helps control the growth of bubbles and prevents them from being too large, thereby obtaining smaller and more uniform pores, which can reduce the risk of rupture during high-temperature heat treatment, which helps to reduce the thermal conductivity of the aerogel and improve its mechanical properties.
[0025] 4) The pore structure formed under low temperature conditions is more uniform and stable. After high-temperature heat treatment, the microstructure of the aerogel is more compact, which helps to improve its thermal stability and durability.
[0026] Through the above effects, the physical cooling properties of dry ice play a key role in the low-temperature assisted sol-gel forming process, providing an effective way to prepare silicon carbide aerogels with high porosity, low thermal conductivity and good mechanical properties.
[0027] Furthermore, the aging treatment time in step S4 is 18 to 36 hours, and the number of replacements with alcohol solvents is 4 to 10 times; the alcohol solute in step S4 is one or more of methanol, ethanol or isopropanol.
[0028] It should be noted that the aging process can further cross-link the polymer chains in the sol, enhance the mechanical stability of the gel, and lay the foundation for subsequent drying and heat treatment, so that it is not easy to collapse and deform during the drying and heat treatment process. The alcohol solvent replacement process can replace the water in the gel with alcohol solvent, reduce the surface tension during the drying process, avoid the collapse of the gel structure, and help maintain the porous structure.
[0029] Normal pressure drying can remove the solvent in the gel to form a dry aerogel. Due to the previous alcohol replacement, the shrinkage during the drying process can be reduced and the porous structure of the aerogel can be maintained. Compared with freeze drying or vacuum drying, normal pressure drying not only reduces the drying conditions and facilitates operation, but also can better maintain the porous structure of the aerogel, avoid the collapse and deformation of the aerogel pore structure caused by changes in temperature and pressure, and effectively improve the pore uniformity, porosity and mechanical properties of the aerogel.
[0030] Further, the temperature of the high temperature heat treatment described in step S5 is 1400°C to 1600°C. High temperature heat treatment can remove organic components in the aerogel and form a stable silicon carbide structure. The high temperature of 1400°C to 1600°C is sufficient to carbonize the organic components and form Si-C bonds, thereby improving the thermal stability and mechanical strength of the aerogel. Optionally, the high temperature heat treatment can be performed under the protection of an inert atmosphere.
[0031] Through the above steps, the preparation method of the present invention not only increases the porosity of silicon carbide aerogel and reduces the thermal conductivity, but also improves the mechanical properties of aerogel through the assistance of physical methods, making it more suitable as a high-performance thermal insulation material.
[0032] The present invention also provides a silicon carbide aerogel prepared by the method for preparing silicon carbide aerogel under low temperature conditions. The silicon carbide aerogel has large porosity, uniform pore structure, good thermal insulation performance and excellent mechanical properties.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0034] 1. The present invention mixes carbosilane with a polymer, introduces dry ice into the sol preparation system, and then controls the reaction rate by low temperature to slow down the silicon carbide aerogel forming rate. The system contains carbon dioxide cold bubbles. These preparation conditions effectively control the internal pore structure of the silicon carbide aerogel, with a small density and high porosity, and a relatively small thermal conductivity. At the same time, its mechanical properties are improved, making the silicon carbide aerogel more practical.
[0035] 2. The present invention simultaneously places appropriate amounts of dry ice inside and outside the incubator, which can control the reaction rate of the gel system by lowering the temperature of the reaction system, and increase the gas content in the gel by introducing dry ice, thereby increasing the porosity. On this basis, the pore structure and porosity of the silicon carbide aerogel can be adjusted by controlling the amount of the gel system and dry ice introduced; the synergistic effect of the two aspects significantly increases the pore volume and porosity of the aerogel, reduces the thermal conductivity, and improves its mechanical properties.
[0036] 3. The present invention introduces non-toxic and tasteless dry ice into the sol system. The physical cooling method of cooling by dry ice is relatively energy-saving. The low temperature condition can reduce the volatilization of volatile reagents. There is no residue after the dry ice evaporates, and no new impurities are introduced. The reaction rate of the reaction system can be regulated. In general, the silicon carbide aerogel prepared by the present invention under low temperature conditions has a large porosity, good thermal insulation performance, simple and cheap raw materials, simple operation, easy control, and cost saving. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present disclosure, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0038] Figure 1 This is a scanning electron microscope image of the silicon carbide aerogel prepared in Example 1;
[0039] Figure 2 This is the X-ray diffraction result of the silicon carbide aerogel prepared in Example 1. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present disclosure to clearly and completely describe the technical solutions in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] The "parts" indicated in the following examples are all parts by weight.
[0045] The method for preparing silicon carbide aerogel under low temperature conditions disclosed in the present invention includes the steps of sol preparation, gel forming, aging treatment, solvent replacement, drying and heat treatment. Specifically, the method includes the following five steps. In step S1, hydroquinone is dissolved in a mixture of water and ethanol, and stirred evenly to obtain solution A; in step S2, formaldehyde, silicate and 3-aminopropyltriethoxysilane are evenly mixed to obtain solution B; in step S3, an insulation box is placed in the foam box, and appropriate amounts of crushed dry ice particles are placed inside and outside the insulation box, respectively, and solution A and solution B are slowly poured into the insulation box, and stirred and mixed evenly to form a sol; in step S4, after the mixed sol is gelled, it is aged, and then replaced with an alcohol solvent and dried at normal pressure; in step S5, high-temperature heat treatment is performed to obtain silicon carbide aerogel. Among them, steps S1 and S2 belong to the sol preparation stage, and step S3 belongs to the gel forming stage. In the sol preparation stage, the pore structure and porosity can be regulated by selecting appropriate solute, solvent type and solute, solvent component ratio to control the concentration and viscosity of the sol. Introducing dry ice in the gel forming stage can not only reduce the temperature to control the reaction rate, but also add carbon dioxide gas to the sol preparation system. The present invention plays a proper role in promoting the regulation of pore structure and porosity by controlling the gel system and introducing dry ice.
[0046] Specifically, the hydroquinone in step S1 is one or more of hydroquinone, resorcinol or catechol, and the following embodiments are described by taking the hydroquinone as resorcinol as an example. The water in step S1 is one of deionized water, distilled water or ultrapure water.
[0047] Specifically, the weight ratio of hydroquinone, formaldehyde, silicate and 3-aminopropyltriethoxysilane is (2-3): (1-3): (4-9): (1-4). The silicate in step S2 is one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or butyl orthosilicate. In the subsequent embodiments, the silicate is ethyl orthosilicate as an example for explanation.
[0048] Specifically, in step S3, magnetic stirring is performed for 20 to 30 minutes. The size of the dry ice particles placed in and / or outside the incubator is about 0.5×0.5×0.5 cm 3 ~1×1×1cm 3Alternatively, in step S3, instead of using a foam box filled with dry ice, the insulated box may be placed in another low-temperature environment to maintain the ambient temperature at -80 to 10°C.
[0049] Specifically, the aging treatment time in step S4 is 18 to 36 hours, and the number of replacements of the alcohol solvent used is 4 to 10 times. The alcohol solute in step S4 is one or more of methanol, ethanol or isopropanol. The temperature of the high temperature heat treatment in step S5 is 1400°C to 1600°C.
[0050] Optionally, in step S1, 20 to 25 parts of resorcinol are weighed and dissolved in 15 to 30 parts of water and 200 to 400 parts of ethanol and mixed evenly to obtain solution A; in step S2, 10 to 20 parts of formaldehyde, 40 to 70 parts of ethyl orthosilicate, and 10 to 20 parts of 3-aminopropyltriethoxysilane are weighed and mixed evenly at room temperature to obtain solution B.
[0051] Optionally, in step S1, 20 to 25 parts of resorcinol are weighed and dissolved in 15 to 40 parts of water and 200 to 500 parts of ethanol and mixed evenly to obtain solution A; in step S2, 10 to 25 parts of formaldehyde, 40 to 80 parts of ethyl orthosilicate, and 20 to 30 parts of 3-aminopropyltriethoxysilane are evenly mixed at room temperature to obtain solution B.
[0052] Optionally, in step S1, 25 to 30 parts of resorcinol are weighed and dissolved in 15 to 50 parts of water and 200 to 600 parts of ethanol and mixed evenly to obtain solution A; in step S2, 10 to 30 parts of formaldehyde, 40 to 90 parts of ethyl orthosilicate, and 30 to 40 parts of 3-aminopropyltriethoxysilane are weighed and mixed evenly at room temperature to obtain solution B.
[0053] Example 1
[0054] A method for preparing silicon carbide aerogel under low temperature conditions comprises the following steps: weighing 20 parts of resorcinol, dissolving it in 15 parts of water and 200 parts of ethanol, and stirring and mixing at room temperature to obtain solution A; sealing and uniformly mixing 10 parts of formaldehyde, 40 parts of ethyl orthosilicate, and 10 parts of 3-aminopropyltriethoxysilane at room temperature to obtain solution B; placing an insulation box in a foam box, placing appropriate amounts of crushed dry ice particles inside and outside the insulation box respectively, slowly pouring solution A and solution B into the insulation box, mixing and stirring for 30 minutes under the action of magnetic stirring to form silicon carbide aerogel material, and stirring and mixing evenly; after the mixed sol is gelled, performing aging treatment for 24 hours, then replacing it with ethanol 8 times, and then drying it at normal pressure; finally performing high-temperature heat treatment at 1500°C to obtain silicon carbide aerogel.
[0055] The silicon carbide aerogel prepared in this embodiment was observed under a scanning electron microscope, and the results obtained are as follows: Figure 1As shown, it can be seen that the silicon carbide aerogel prepared by the present invention has an obvious porous structure; the silicon carbide aerogel prepared in this embodiment is tested by X-ray diffraction (XRD), and the results are as follows Figure 2 As shown, it can be seen that it has an obvious crystal peak, and its silicon carbide structure can be confirmed based on the peak position.
[0056] Example 2
[0057] A method for preparing silicon carbide aerogel under low temperature conditions comprises the following steps: weighing 25 parts of resorcinol, dissolving it in 30 parts of water and 300 parts of ethanol, and stirring and mixing at room temperature to obtain solution A; sealing and uniformly mixing 20 parts of formaldehyde, 60 parts of ethyl orthosilicate, and 20 parts of 3-aminopropyltriethoxysilane at room temperature to obtain solution B; placing an insulation box in a foam box, placing appropriate amounts of crushed dry ice particles inside and outside the insulation box respectively, slowly pouring solution A and solution B into the insulation box, mixing and stirring for 25 minutes under the action of magnetic stirring to form silicon carbide aerogel material, and stirring and mixing evenly; after the mixed sol is gelled, performing aging treatment for 28 hours, then replacing it with ethanol for 4 times, and then drying it at normal pressure; finally performing high-temperature heat treatment at 1500°C to obtain silicon carbide aerogel.
[0058] Example 3
[0059] A method for preparing silicon carbide aerogel under low temperature conditions comprises the following steps: weighing 30 parts of resorcinol, dissolving it in 40 parts of water and 500 parts of ethanol, and stirring and mixing at room temperature to obtain solution A; sealing and uniformly mixing 30 parts of formaldehyde, 80 parts of ethyl orthosilicate, and 30 parts of 3-aminopropyltriethoxysilane at room temperature to obtain solution B; placing an insulation box in a foam box, placing appropriate amounts of crushed dry ice particles inside and outside the insulation box respectively, slowly pouring solution A and solution B into the insulation box, mixing and stirring for 30 minutes under the action of magnetic stirring to form silicon carbide aerogel material, and stirring and mixing evenly; after the mixed sol is gelled, performing aging treatment for 28 hours, then replacing it with methanol for 4 times, and then drying it at normal pressure; finally performing high-temperature heat treatment at 1500°C to obtain silicon carbide aerogel.
[0060] Example 4
[0061] A method for preparing silicon carbide aerogel under low temperature conditions comprises the following steps: weighing 30 parts of resorcinol, dissolving it in 50 parts of water and 600 parts of ethanol, and stirring and mixing at room temperature to obtain solution A; sealing and uniformly mixing 30 parts of formaldehyde, 90 parts of ethyl orthosilicate, and 40 parts of 3-aminopropyltriethoxysilane at room temperature to obtain solution B; placing an insulation box in a foam box, placing appropriate amounts of crushed dry ice particles inside and outside the insulation box respectively, slowly pouring solution A and solution B into the insulation box, mixing and stirring for 30 minutes under the action of magnetic stirring to form silicon carbide aerogel material, and stirring and mixing evenly; after the mixed sol is gelled, performing aging treatment for 24 hours, then replacing it with isopropanol 6 times, and then drying it at normal pressure; finally performing high-temperature heat treatment at 1600°C to obtain silicon carbide aerogel.
[0062] Comparative Example 1
[0063] This comparative example is based on Example 1, and the difference from Example 1 is that dry ice is not used in this comparative example. The specific steps are as follows:
[0064] Weigh 20 parts of resorcinol and dissolve it in 15 parts of water and 200 parts of ethanol, and stir and mix at room temperature to obtain solution A; 10 parts of formaldehyde, 40 parts of ethyl orthosilicate, and 10 parts of 3-aminopropyltriethoxysilane are sealed and uniformly mixed at room temperature to obtain solution B; put an insulation box into the foam box, slowly pour solution A and solution B into the insulation box, mix and stir for 30 minutes under the action of magnetic stirring to form silicon carbide aerogel material, and stir and mix evenly; after the mixed sol is gelled, it is aged for 24 hours, and then replaced with ethanol 8 times and dried at normal pressure; finally, it is subjected to high-temperature heat treatment at 1500°C to obtain silicon carbide aerogel.
[0065] Comparative Example 2
[0066] This comparative example is based on Example 1, and the difference from Example 1 is that this comparative example only places dry ice inside the incubator. The specific steps are as follows:
[0067] Weigh 20 parts of resorcinol and dissolve it in 15 parts of water and 200 parts of ethanol, and stir and mix at room temperature to obtain solution A; 10 parts of formaldehyde, 40 parts of ethyl orthosilicate, and 10 parts of 3-aminopropyltriethoxysilane are sealed and uniformly mixed at room temperature to obtain solution B; put an insulation box in the foam box, and only put an appropriate amount of crushed dry ice particles in the insulation box, slowly pour solution A and solution B into the insulation box, mix and stir for 30 minutes under the action of magnetic stirring to form silicon carbide aerogel material, and stir and mix evenly; after the mixed sol is gelled, it is aged for 24 hours, and then replaced with ethanol 8 times and dried at normal pressure; finally, it is subjected to high-temperature heat treatment at 1500°C to obtain silicon carbide aerogel.
[0068] Comparative Example 3
[0069] This comparative example is based on Example 1, and the difference from Example 1 is that in this comparative example, only dry ice is placed outside the incubator. The specific steps are as follows:
[0070] Weigh 20 parts of resorcinol and dissolve it in 15 parts of water and 200 parts of ethanol, and stir and mix at room temperature to obtain solution A; 10 parts of formaldehyde, 40 parts of ethyl orthosilicate, and 10 parts of 3-aminopropyltriethoxysilane are sealed and uniformly mixed at room temperature to obtain solution B; an insulation box is placed in a foam box, and only a proper amount of crushed dry ice particles are placed outside the insulation box, and solution A and solution B are slowly poured into the insulation box and mixed and stirred for 30 minutes under the action of magnetic stirring to form a silicon carbide aerogel material, and the mixture is stirred and mixed uniformly; after the mixed sol is gelled, it is aged for 24 hours, and then replaced with ethanol 8 times and dried at normal pressure; finally, a high-temperature heat treatment at 1500°C is performed to obtain silicon carbide aerogel.
[0071] Comparative Example 4
[0072] This comparative example is based on Example 1, and the difference from Example 1 is that this comparative example uses vacuum freeze drying to replace the normal pressure drying in Example 1. The specific steps are as follows:
[0073] Weigh 20 parts of resorcinol and dissolve it in 15 parts of water and 200 parts of ethanol, and stir and mix at room temperature to obtain solution A; 10 parts of formaldehyde, 40 parts of ethyl orthosilicate, and 10 parts of 3-aminopropyltriethoxysilane are sealed and uniformly mixed at room temperature to obtain solution B; an insulation box is placed in a foam box, and appropriate amounts of crushed dry ice particles are placed inside and outside the insulation box respectively, and solution A and solution B are slowly poured into the insulation box and mixed and stirred for 30 minutes under the action of magnetic stirring to form a silicon carbide aerogel material, and the mixture is stirred and mixed uniformly; after the mixed sol is gelled, it is aged for 24 hours, and then replaced with ethanol 8 times and then vacuum freeze-dried; finally, a high-temperature heat treatment at 1500°C is performed to obtain silicon carbide aerogel.
[0074] Table 1 Performance data of silicon carbide aerogels prepared in Examples 1-4 and Comparative Examples 1-4
[0075] Sample No. <![CDATA[Thermal conductivity W / (m . k)]]> <![CDATA[Density g / cm 3 > Porosity Example 1 0.028 0.24 95% Example 2 0.035 0.31 93% Example 3 0.036 0.32 90% Example 4 0.041 0.35 89% Comparative Example 1 0.065 0.59 75% Comparative Example 2 0.047 0.38 82% Comparative Example 3 0.040 0.34 83% Comparative Example 4 0.030 0.28 93%
[0076] It can be seen from Table 1 that the silicon carbide aerogel prepared in Example 1 has higher porosity and compressive strength, lower thermal conductivity and density than Comparative Examples 1-4, and the silicon carbide aerogel prepared in Examples 2-4 has higher porosity and compressive strength, and lower thermal conductivity and density than Comparative Examples 1-3. It is confirmed that the aerogel prepared by the method for preparing silicon carbide aerogel under low temperature conditions described in the present invention can significantly reduce its thermal conductivity and density and increase its porosity.
[0077] Compared with Example 1, the thermal conductivity and density of Comparative Examples 1-4 increased to varying degrees, and the porosity decreased to varying degrees, which confirmed that the addition of dry ice, the addition of dry ice inside and outside the insulated box, and the drying method of normal pressure drying can significantly reduce the thermal conductivity and density of the obtained silicon carbide aerogel, increase the porosity, and achieve significant technical effects.
[0078] It can be seen that the present invention provides a new method for preparing silicon carbide aerogel, which realizes the effective regulation of pore structure, porosity, thermal conductivity and mechanical properties through the dry ice-assisted sol-gel forming process, and provides new possibilities for the research and application of silicon carbide aerogel materials.
[0079] The above are only several embodiments of the present disclosure. Those skilled in the art may make various changes or modifications to the embodiments of the present disclosure based on the contents disclosed in the application documents without departing from the spirit and scope of the present disclosure.
Claims
1. A method for preparing silicon carbide aerogel under low temperature conditions, characterized in that: The following steps are involved: S1. dissolving hydroquinone in a mixture of water and ethanol, and stirring to obtain a solution A; S2, uniformly mixing formaldehyde, silicate and 3-aminopropyltriethoxysilane to obtain solution B; S3, provide an incubator with an ambient temperature of -80~10°C, put crushed dry ice particles in the incubator, then slowly pour solution A and solution B into the incubator, stir and mix evenly to form a sol; S4, after the mixed sol is gelled, it is subjected to aging treatment, and then replaced with an alcohol solvent and dried at normal pressure; S5. Finally, high temperature heat treatment is performed to obtain silicon carbide aerogel.
2. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 1, characterized in that: The catechol described in step S1 is one or more of hydroquinone, resorcinol or catechol.
3. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 2, characterized in that: The weight ratio of water to ethanol in step S1 is 1:(10-20).
4. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 2, characterized in that: The weight ratio of the hydroquinone, formaldehyde, silicate and 3-aminopropyltriethoxysilane is (2-3):(1-3):(4-9):(1-4).
5. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 2, characterized in that: The silicate in step S2 is one or more of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate or butyl orthosilicate.
6. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 5, characterized in that: The stirring in step S3 is magnetic stirring, and the stirring time is 20 to 30 minutes.
7. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 5, characterized in that: The aging treatment time in step S4 is 18 to 36 hours.
8. The method for preparing silicon carbide aerogel under low temperature conditions according to claim 6, characterized in that: The number of replacements with alcohol solvents in step S4 is 4 to 10 times.
9. The method for preparing silicon carbide aerogel under low temperature conditions according to any one of claims 1 to 8, characterized in that: The temperature of the high temperature heat treatment in step S5 is 1400°C to 1600°C.
10. Silicon carbide aerogel prepared by the method for preparing silicon carbide aerogel under low temperature conditions as claimed in any one of claims 1 to 9.